HUBUNGAN PENGETAHUAN IBU DENGAN PELAKSANAAN IMUNISASI DASAR PADA BAYI DI DESA KARANG SARI HUTA 3 KECAMATAN GUNUNG MALIGAS KABUPATEN SIMALUNGUN - Maimunah, Maimunah (JURNAL KELUARGA SEHAT SEJAHTERA, 2017)
ABSTRACT The objective of the research was to find out the correlation between mothers™ knowledge and the implementation of basic immunization at Karang Sari Huta 3 Village, Gunung Maligas Subdistrict, Simalungn District. The research was quantitative correlation design. The population was al mothers who had babies at Karang Sari Huta 3, and the samples were 53 10-12 month-old babies. The data were gathered by distributing questionnaires and analyzed by using Spearman Rank (Rho) correlation test. The result of the research showed that the result of Spearman Rank (Rho) correlation test was 0.576 at the significance level of 1% and p-value < Î± (0.000 < 0.01) so that Ho was rejected and Ha was accepted which indicated that there was positive correlation between mothers™ knowledge and the implementation of basic immunization in babies at Karang Sari Huta 3 Village, Gunung Maligas Subdistrict, Simalungun District. It is recommended that health care providers at this village improve health service by using the procedure and schedules about giving basic immunization to babies. Kata Kunci: Pengetahuan, Pelaksanaan Imunisasi Dasar